THE WORKING CAPITAL MANAGEMENT ON FINANCIALLY CONSTRAINED FIRM - Ninditya Nareswari; Nuraini Desty Nurmasari (Jurnal Bisnis dan Keuangan, 2021)
Working capital management is a daily activity that will determine the availability of resources for the company. There are positive and negative effects in increasing the degree of working capital. There is an optimal degree as well. The degree of optimal working capital for each company is different, depends on financial conditions. This paper aims to examine the effect of non-linear working capital on firm performance and analyze the differences in the degree of optimal working capital between financially constrained and unconstrained firms. Data were obtained from OSIRIS with the observation period 2010-2019. Working capital is proxied by the net trade cycle. This study uses panel data regression models, i.e. fixed effect regression and random effect regression. The result of this study shows that working capital has a non-linear effect (U-shaped inverted) on firm performance when using ROA and ROE as a proxy for performance which means the company has an optimal degree of working capital. The result also shows that financially constrained firms grouped based on cash flow, interest coverage, and cost of external financing have lower optimal working capital which means that the benefits of working capital are more used by non-financially constrained firms.